Some Methods of Signal Processing and Beamforming in Hydrographic Applications - Ruuben, T.; Derkats, J. (Elektronika ir Elektrotechnika, 2008)
Some signal processing and beamforming methods for hydrographic applications are presented. Some additional signals and processing methods as part of the bathymetric data collection to determine the new measurement techniques will be discussed. Optimal binary sequences are used for sounding signal generation, leading to an increase system resolution. The dynamics of the spread spectrum signals in sensor array models with the optimum reception methods will be described. The advanced FFT beamforming will be compared with the block-phase beamforming method in terms of the practical realization approach. Ill. 10, bibl. 13 (in English; summaries in English, Russian and Lithuanian).